Improving Effectiveness of State Management Using Prop Drilling Pattern on Jala Tech's Financial Feature - Erdanto, Albarra Naufala; Sujarwo, Ari (Proceeding International Conference on Religion, Science and Education, 2022)
Jala Tech is a technology company that helps shrimp farmers in improving the quality of their ponds by utilizing web-based applications. One of the features of the Jala web application is the financial feature. State management in the frontend code of the feature uses the event bus pattern. However, there is a problem with implementing the event bus, namely the inability of Vue Devtools to debug the state. This inability makes it difficult for developers to track the flow of state changes in the application view. In addition, the decentralized method in storing application states causes state redundancy to occur in components that use the same state. Based on this, it is necessary to rewrite the code on the financial feature to change the state management from using the event bus pattern to the prop drilling pattern. The result of this research is a financial feature that has implemented prop drilling in the frontend code. By using prop drilling, it is possible to debug the state using Vue Devtools and centralize the states on the main parent component of the financial feature of the Jala web application. Therefore, developers can track state changes and more easily identify the state used in the financial feature of the Jala web application.